Metals (+2) complexes with 2-acyl-derivatives of indandione - A. N. Kochetov; L. Yu. Alikberova; К. А. Shestakov (Тонкие химические технологии)
Complexes of Be(II), Mg(II), Zn(II), Co(II), Pd(II), Cu(II)) with 2(diphenylacetyl)- indandione-1,3 and (2-phenyl-4-chlorphenylacetyl)indandione-1,3 are synthesized and studied by various methods. These compounds are isostructural innercoordinated salts with deprotonated ligand form